Let the records speak: an exploration of rehabilitation services offered in primary healthcare, Johannesburg metropolitan district - Lebogang Maseko; Fasloen Adams; Hellen Myezwa (BMC, 2024)
Abstract Background Primary healthcare in South Africa aims to transform the national health system by emphasising community-based care and preventive strategies. However, rehabilitation services, particularly for individuals with disabilities and chronic non-communicable diseases, are often overlooked in primary healthcare. This study aimed to investigate the provision of primary healthcare rehabilitation services in the Johannesburg Metropolitan District by exploring client sociodemographics and variations in services provided by rehabilitation professionals. Methods A retrospective review of clinic rehabilitation records from 2011 to 2020 was conducted at nine provincially funded community health centres (CHCs) offering rehabilitation services. Stratified sampling facilitated record selection based on rehabilitation service type and year. A specifically designed data extraction tool captured demographics, disabilities, rehabilitation received, and referral sources. Descriptive analysis used means, standard deviations, and frequencies. Results The findings show a diverse client population with a wide age range, with a significant proportion falling into the < 5 years and 30-49 years age groups. Neuromusculoskeletal and movement-related disabilities were most prevalent, affecting approximately two-thirds of clients. Referral sources were often undocumented, and inconsistent discharge information with no record of patient follow up, highlighted the need for improved documentation practices. Clinic visits were the primary service delivery mode, followed by limited home visits and outreach services. Occupational therapy and physiotherapy were the most used services. Speech and language therapy services were underused, and some CHCs lacked audiology services. There were variations in the number of individual and group sessions provided by the different rehabilitation services, and there were age- and disability-specific differences in service use. Conclusion This study offers insights into rehabilitation service provision in the Johannesburg Metropolitan District and enhances our understanding of rehabilitation services in primary healthcare settings. It underscores the importance of a multidisciplinary rehabilitation team to address diverse rehabilitation needs, improving documentation and discharge practices, expanding service delivery models, and reducing disparities in service use. The findings inform strategies for optimising service delivery, workforce, resource allocation, and intersectoral collaboration to ultimately enhance the quality and accessibility of integrated rehabilitation services.